2017
DOI: 10.1177/0898010117720341
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Experiences of Grief Following Patient Death: A Qualitative Approach

Abstract: The study provided evidence that nurses respond emotionally to patients' death and experience grief. Nurses are burdened by recurrent patients' deaths and try to cope and overcome their grief. This study emphasizes the importance of developing strategies to help nurses positively cope with their grief from a holistic perspective. This will reflect positively on the nurses' performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 44 publications
4
41
1
7
Order By: Relevance
“…According to scientists from Jordan, the feelings that are provoked by the death of a patient are most often sadness and sorrow. Additionally, religion and spirituality are very important while dealing with emotions, 23 which is also confirmed by Makowicz et al 22 and MacDermott and Keenan. 24 According to the author of this study, some persons chose religion as a stress-coping strategy.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…According to scientists from Jordan, the feelings that are provoked by the death of a patient are most often sadness and sorrow. Additionally, religion and spirituality are very important while dealing with emotions, 23 which is also confirmed by Makowicz et al 22 and MacDermott and Keenan. 24 According to the author of this study, some persons chose religion as a stress-coping strategy.…”
Section: Discussionmentioning
confidence: 64%
“…Additionally, it can be noticed that the resistance to stress comes with experience. 23 Lien et al 32 also show that seniority is a crucial factor in choosing the strategies and methods of coping with patients' death. Experience in hospice care is an important predictor of the life attitude of the nurses employed in the intensive care unit and it influences self-efficacy in response to death.…”
Section: Discussionmentioning
confidence: 99%
“…McCallin (2011McCallin ( , p. 2331 found that nurses caring for patients at the end of life went beyond the "efficiency-effectiveness rhetoric to engage in meaningful 'being with' relationships" with patients, thereby emphasizing moral responsibilities in the patient-provider relationship. Staff who engage with residents in NHs therefore likely to experience suffering, loss, grief, and bereavement when the residents die (Boerner et al, 2015;Cagle et al, 2017;Khalaf et al, 2018;Marcella & Kelley, 2015;Simard, 2020). Van Riesenbeck et al (2015) found that a resident's death may be perceived by care providers as akin to the loss of a loved one and that they may feel emotionally unprepared for it.…”
Section: Background and Significancementioning
confidence: 99%
“…The results showed that limited experience and knowledge tend to make them helpless, whereas the majority of them try their level best to focus on positives after the death of a child in their care. The grief experiences by nurses have not been addressed within the practice setting; therefore, it is necessary to show that nurses respond emotionally to patients' death and experience grief (Khalaf et al, 2017). The experiences of grief among the nurses about emotional labor and death of the patient (child) are part of their work that affects their personal as well as professional lives (Granek et al, 2015).…”
Section: Resultsmentioning
confidence: 99%